Neurophysiological confirmation of phrenic nerve affection in a patient with dyspnea and herpes zoster - Martić, Vesna; Stojanov, Aleksandar (Vojnosanitetski pregled, 2023)
Introduction. Herpetic lesion of the phrenic nerve is quite uncommon. These lesions are usually unilateral, and for most clinicians, the clinical manifestation of herpes zoster in the cervical or thoracic region and diaphragmatic paralysis on the same side is sufficient for making a diagnosis of segmental herpes zoster phrenic nerve palsy. We report a patient with a classic clinical picture, in which we confirmed phrenic nerve affection on nerve conduction study. Case report. A 58-year-old female patient came for an examination due to shortness of breath. The patient had a herpetic rash on her right shoulder two and a half months earlier. The elevation of the right hemidiaphragm was seen on chest X-ray imaging. Asymmetry was evident in the nerve conduction study of the phrenic nerve: prolonged latency and reduced amplitude of her right phrenic nerve. The patient was treated with acyclovir, pregabalin, and B complex vitamins. After six months, the motor deficit was reduced completely. Conclusion. A nerve conduction study of the phrenic nerve is useful in making the definitive diagnosis. Good outcome, as in this patient, is rare in patients with this diagnosis and may be linked to timely treatment with acyclovir.
Keywords: diagnosis; electrodiagnosis; herpes zoster; nerve conduction studies; phrenic nerve